If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + x + 2 = 2x + -4 Reorder the terms: 2 + 3x + x = 2x + -4 Combine like terms: 3x + x = 4x 2 + 4x = 2x + -4 Reorder the terms: 2 + 4x = -4 + 2x Solving 2 + 4x = -4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 2 + 4x + -2x = -4 + 2x + -2x Combine like terms: 4x + -2x = 2x 2 + 2x = -4 + 2x + -2x Combine like terms: 2x + -2x = 0 2 + 2x = -4 + 0 2 + 2x = -4 Add '-2' to each side of the equation. 2 + -2 + 2x = -4 + -2 Combine like terms: 2 + -2 = 0 0 + 2x = -4 + -2 2x = -4 + -2 Combine like terms: -4 + -2 = -6 2x = -6 Divide each side by '2'. x = -3 Simplifying x = -3
| 31-9(y+5)=7 | | x^3-96x^2+576x=0 | | -17-9=8x+17 | | 7y-9=33 | | 4x24= | | 5(2x-1)+16=8x+1 | | 3x+1=2x-1 | | -24=6a-15-15a | | 10-10x=75-45x | | 5x-4=-4+5x | | x^4-x^3+1=0 | | 5x=4(x+3) | | 5a-9=26 | | 1=14(2r+1) | | 14-6x=2x+66 | | 8x+29x-6= | | 1.4m-06(m-2)=2.4m | | 2x+40=12x-40 | | 5x-4=2x+6+x | | 37x=9x+4 | | 2(x-7)=10-4x | | 25x^2-15x-4=0 | | 12-6x=6x+34 | | 6x-10=46 | | 2+5+6rs= | | 2(y-6)-(y+2)=26 | | (x^2+16)(x^3-108)=0 | | 14a+12=84 | | 9[(4+4)-2]= | | .1(x^2+16)(x^3-108)=0 | | 4=5-3x | | -5(t-4)-7= |